Treatment of COVID-19 in Pregnancy with Hydroxychloroquine and Azithromycin: a case report - Sisti, Giovanni; Schiattarella, Antonio; Sisti, Andrea (Acta Biomedica Atenei Parmensis, 2020)
The combination of hydroxychloroquine (HCQ) and azithromycin could represent a suitable treatment for SarS-CoV-2 positive pregnancies. The authors report one of the first cases of COVID-19 positive pregnant woman successfully treated with HCQ in April 2020.